Temporal Landscape Perceptions and Preferences for Tourism Development at the Teaching Factory of Politeknik Negeri Jember - Pertami, Rindha Rentina Darah; Farhan, Muhamad; Wardani, Peni Arianita; Jumiatun, Jumiatun; Fibriani, Suwinda; Widiyanti, Della (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
The development of Teaching Factory as an educational landscape Tourism is a strategic step to bring education as a synchronization of learning activities that refers to Merdeka Belajar Kampus Merdeka. Tourism is related to the beauty and relationship of the landscape between its elements. Perceptions and preferences for beauty are needed as a basis for developing a tourist area. The scenic beauty estimation (SBE) method will enable you to evaluate a landscape. Time is one of the landscape elements that will enhance the character of the landscape. The worst landscape is Landscape 19, which was the parking lot for the Department of Language, Communication, and Tourism. The perception of the respondent's memory that states that the Health Department is the landscape with the best value is based on the time when the picture was taken during the day, which is the perfect time in terms of lighting, shadows, and composition. Another thing is that the health department is an icon of Politeknik Negeri Jember.